Staging model for amyotrophic lateral sclerosis in Singapore - Yuan Teck Tay; Josiah YH Chai; Kamilah Bte Shekh Jabin; Kexin Ang (Singapore Medical Journal)
Introduction: A clinical-based staging model would guide physicians in the prompt management of the evolving symptoms and functional needs of patients with amyotrophic lateral sclerosis (ALS). Methods: We aimed to delineate the clinical trajectory of ALS in Singapore and test the degree of congruity of King’s College staging for ALS (King’s staging) among Singapore patients. In this retrospective cohort study, clinical milestones used for staging were identical to King’s staging: stage 1 corresponded to symptom onset; stage 2A corresponded to diagnosis; stage 2B corresponded to two central nervous system (CNS) regions; stage 3B corresponded to three CNS regions; stage 4A corresponded to requirement of supportive enteric feeding; and stage 4B corresponded to requirement of non-invasive ventilation, of which bulbar, diaphragmatic, upper and lower limb pyramidal involvements each constituted one CNS region. Standardised timings from disease onset (0) to death (1) among Singapore patients with ALS were measured. Results: 46 patients with ALS were reviewed. Results were largely congruous with King’s staging. Results for patients with limb-onset. ALS were: diagnosis (0.35); two CNS region involvement (0.42); three CNS region involvement (0.63); diaphragmatic involvement (0.81); and bulbar involvement (0.73). Results for patients with bulbar-onset. ALS were: diagnosis (0.14); two CNS region involvement (0.28); three CNS region involvement (0.42); diaphragmatic involvement (0.62); and bulbar involvement (0.67). Conclusion: King’s staging can be used to model ALS trajectory in Singapore due to the large degree of congruity seen. Easily remembered and accessible knowledge of ALS staging will allow prompt management of the evolving needs of patients with ALS.